EWaS3 2018 2018
DOI: 10.3390/proceedings2110656
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Concentrations in Seven Irrigation Reservoirs (Lake Karla Watershed Thessaly Greece)

Abstract: The construction of irrigation reservoirs is a technical global solution for enhancing the agricultural production especially in arid and semi-arid areas. These water bodies are treated as technical projects and not as freshwater ecosystems. Eutrophication in new reservoirs becomes a hot issue in the world. The aim of the present study is to present the assessment of the key-eutrophication parameters in seven reservoirs located in the catchment area of Lake Karla. We suggest that the studied artificial ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Asefa et al (2013) reported a value of 0.5 mg L −1 from Angereb reservoir; Wassie and Melese also reported NO 3 − concentrations ranged from 0.1 to 2.0 mg L −1 from Selameko man-made Reservoir (Wassie and Melese 2017). Similarly, its level lower than the values reported from Greece (Chamoglou et al 2018), Portugal (Palma et al 2014) and from Ghana (Boadi et al 2020). The values are comparable with reports for some dams in Saudi Arabia (Albaggar 2021), Ondo State, Gilgel Gibe Reservoir, Ethiopia, concentration ranged from 0.62 to 0.69 (Woldeab et al 2018), Adesakin (0.3-5.32 mg L −1 ) of water reservoir reported from Nigeria (Adesakin et al 2020), and Garra River, India, with NO 3 − values ranged from 0.03 to 3.79 mg L −1 (Khan and Wen 2021).…”
Section: Concentrations Of Nutrients From Angereb Reservoirmentioning
confidence: 93%
“…Asefa et al (2013) reported a value of 0.5 mg L −1 from Angereb reservoir; Wassie and Melese also reported NO 3 − concentrations ranged from 0.1 to 2.0 mg L −1 from Selameko man-made Reservoir (Wassie and Melese 2017). Similarly, its level lower than the values reported from Greece (Chamoglou et al 2018), Portugal (Palma et al 2014) and from Ghana (Boadi et al 2020). The values are comparable with reports for some dams in Saudi Arabia (Albaggar 2021), Ondo State, Gilgel Gibe Reservoir, Ethiopia, concentration ranged from 0.62 to 0.69 (Woldeab et al 2018), Adesakin (0.3-5.32 mg L −1 ) of water reservoir reported from Nigeria (Adesakin et al 2020), and Garra River, India, with NO 3 − values ranged from 0.03 to 3.79 mg L −1 (Khan and Wen 2021).…”
Section: Concentrations Of Nutrients From Angereb Reservoirmentioning
confidence: 93%